2002
DOI: 10.1021/es010323a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in Vivo and in Vitro Reporter Gene Assays for Short-Term Screening of Estrogenic Activity

Abstract: CALUX assay, only o,p′-DDT demonstrated weak dose-related estrogenic activity in vivo. To determine if differences in reporter gene activity may be explained by differential affinity of (xeno)estrogens to human and zebrafish ERs, fulllength sequences of the zebrafish ER subtypes R, , and γ were cloned, and transactivation by (xeno)estrogens was compared to human ERR and ER . Using transiently transfected recombinant ER and reporter gene constructs, EE2 also showed relatively potent activation of zebrafish ERR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 34 publications
13
130
1
3
Order By: Relevance
“…This finding is different from data published by Legler et al (2002) who found that all three of the zf ERs, including ERba (ERg in their report) were responsive. The pattern of ER inducibility was also different between bass and zf.…”
Section: Differential Activation Of Lmb Er Subtypes By E 2 and Npcontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is different from data published by Legler et al (2002) who found that all three of the zf ERs, including ERba (ERg in their report) were responsive. The pattern of ER inducibility was also different between bass and zf.…”
Section: Differential Activation Of Lmb Er Subtypes By E 2 and Npcontrasting
confidence: 99%
“…Recently, three ER isotypes have been shown to exist in fish as reported by us and others (Hawkins et al 2000, Legler et al 2002, Sabo-Attwood et al 2004, Filby & Tyler 2005. The three ERs, originally termed ERa, ERb, and ERg, were recently renamed ERa, ERbb, and ERba respectively, to comply with official zebrafish (zf) nomenclature (Hawkins & Thomas 2004, Filby & Tyler 2005.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…They are excreted by humans and livestock and discharged in the environment with effluents of sewage treatment plants (Kolpin et al 2002;Legler et al 2002;Snyder et al 2003) or with agricultural run off (Lange et al 2002;Johnson et al 2006;Matthiessen et al 2006). Only at certain specific locations, estrogenic activities were partly or fully caused by high concentrations of alkylphenols (Sheahan et al 2002;Fenet et al 2003;Cespedes et al 2004;Quiros et al 2005).…”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%